Siberian Merchants in Mikhail M. Speransky’s Travel Diary and Letters (1819–1821) - Evgeniya V. Komleva (СибСкрипт, 2023)
Mikhail M. Speransky was one of the most outstanding statesman of the Russian Empire. He was the Siberian Governor-General in 1819–1821. His Siberian travel diary and correspondence cast light upon the interaction between state power and private capital during the economic and socio-cultural integration of the Eastern territories. The research objective was to reveal M. M. Speransky’s opinion about Siberian merchants, who were the most influential regional community. The analysis included M. M. Speransky’s brief diary entries and long letters to his daughter and friends, and as well as his business correspondence. M. M. Speransky believed that Siberian merchants were to play an important role in the development of regional economy and society. Numerous contacts with representatives of merchants from different Siberian cities allowed him to make observations about the moods spread in the merchant environment, the volume and features of commercial operations, their social role, etc. He also established good relations with the most prominent merchants. M. M. Speransky wrote about everyday life, culture, and economic relations of Siberian communities. He advocated the freedom of trade and despised the selfish attitude of the local administrations to the merchant class. He gathered information from different sources, including personal conversations with merchants, and developed an opinion on such important state issues as the activities of the Russian-American Company and the Russian-Chinese trade via Kyakhta. M. M. Speransky’s had a pragmatic interest in merchants and encouraged them to make charity donations for various needs.